Analysis Of Dependence Ratio and Open Unemployment Rate Human Development Index In South Sumatra Province - Marina Malian (Journal Arbitrase : Economy, Management and Accounting, 2024)
This study examined the effect of dependency ratio and unemployment rate on the human development index in South Sumatra Province. This study used secondary data with the type of time series data during 2002-2020 obtained from the Central Bureau of Statistics. The data analysis method used was Vector Auto Regression (VAR). The results showed that the HDI did not have a negative and significant effect on themselves, ABK had no negative and significant effect on the HDI, and TPT had no negative and significant effect on the HDI.